Examining the impacts of public transit on healthy aging through a natural experiment: study protocols and lessons learned from the Active El Paso project - Li, Wei; Lee, Chanam; Zhong, Sinan; Xu, Minjie; Towne Jr, Samuel D.; Zhu, Xuemei; Lee, Sungmin; Wang, Suojin; Aldrete, Rafael; Garcia, Eufemia B.; Whigham, Leah; Toney, Ashley M.; et al. (Frontiers in Public Health, 2023)
This paper describes protocols and experiences from a seven -year natural-experiment study in El Paso, Texas, a border city of predominantly Latino/Hispanic population. The study focuses on how Bus Rapid Transit impacts physical activity and thus plays a role in alleviating obesity and related chronic diseases that impact healthy aging. Our protocols describe a longitudinal and case-comparison study, which compared residents exposed to new Bus Rapid Transit (BRT) stations with those who were not. This paper also introduces lessons and experiences to overcome the following challenges: delays in the BRT opening (the main intervention), the COVID-19 pandemic, methodological challenges, participant recruitment and retention , and predatory survey takers. Our transdisciplinary approach was pivotal in addressing these challenges. We also proposed and tested multi-level intervention strategies to reduce modifiable barriers to transit use.Our most important takeaway for researchers, practitioners, and policy makers is the importance of being flexible and ready to adapt to new circumstances. Future natural-experiment researchers need to become more versatile in an increasingly volatile and uncertain world.